2014
DOI: 10.1177/1471301214523280
|View full text |Cite
|
Sign up to set email alerts
|

Caring for older people living alone with dementia: Healthcare professionals’ experiences

Abstract: Older adults living alone with dementia are at greater risk of placement in long-term care homes compared with those living with others. Healthcare professionals have vital roles in supporting them to continue living in the community. Yet, little is known about how healthcare professionals fulfill these roles and what their experiences are like. The study purpose was to describe health care professionals' experiences of caring for older people with dementia living alone. Using a qualitative descriptive approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 57 publications
(98 reference statements)
2
35
0
Order By: Relevance
“…This is similar to other healthcare professionals' experiences, as healthcare professionals working in dementia services highlighted their distress when identifying with family carers, particularly when there were similar elements to their own personal lives (Ducharme, et al 2014). Healthcare professionals have also discussed their distress and emotional struggle alongside their ethical duty to support people with dementia to live in a safe environment, and the need to internalise their actions with the belief they 'did the right thing ' (de Witt, & Ploeg, 2016).…”
Section: Negative Emotional Responses To Dementiasupporting
confidence: 52%
“…This is similar to other healthcare professionals' experiences, as healthcare professionals working in dementia services highlighted their distress when identifying with family carers, particularly when there were similar elements to their own personal lives (Ducharme, et al 2014). Healthcare professionals have also discussed their distress and emotional struggle alongside their ethical duty to support people with dementia to live in a safe environment, and the need to internalise their actions with the belief they 'did the right thing ' (de Witt, & Ploeg, 2016).…”
Section: Negative Emotional Responses To Dementiasupporting
confidence: 52%
“…Very little is known about the effect of receiving a diagnosis of mild cognitive impairment (MCI) or Alzheimer’s disease (AD) for older adults living alone. A recent study [8] reported that older adults living alone with cognitive impairment distrusted and avoided healthcare providers (e.g., physicians, social workers, nurses) whom they believed did not understand their priorities. Providers, on the other hand, described the tension of meeting their responsibilities with their patients living alone with cognitive impairment as “walking the tight rope.” In particular, providers reported their unease about telling patients that they had to stop driving or relocate.…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of "emotional labour" is widely reported among intensive care professionals (Sorensen and Iedema, 2009;Ryan and Seymour, 2013), health care assistants caring for dying cancer patients (Herber and Johnston, 2013;Lovatt et al, 2015); healthcare assistants in inpatient dementia services (Bailey et al, 2015); palliative care nurses (Skilbeck and Payne, 2003) and hospice staff (Sabo, 2008;Slocum-Gori et al, 2011). More recently, Colomer and de Vries (2016) and de Witt and Ploeg (2016) acknowledged that care home workers' emotional bonds with residents with dementia sometimes contributed to feeling physically, mentally and emotionally drained.…”
Section: Introductionmentioning
confidence: 99%